Physical, clinical, and psychosocial parameters of adolescents with different degrees of excess weight - Vanessa Drieli Seron Antonini; Danilo Fernandes da Silva; Josiane Aparecida Alves Bianchini; Carlos Andres Lopera; Amanda Caroline Teles Moreira; João Carlos Locateli; Nelson Nardo Júnior (Sociedade de Pediatria de São Paulo, 2014)
OBJECTIVE: To compare body composition, hemodynamic parameters, health-related physical fitness, and health-related quality of life of adolescents with anthropometric diagnosis of overweight, obesity, and severe obesity.METHODS: 220 adolescents with excess body weight were enrolled. They were beginners in a intervention program that included patients based on age, availability, presence of excess body weight, place of residence, and agreement to participate in the study. This study collected anthropometric and hemodynamic variables, health-related physical fitness, and health-related quality of life of the adolescents. To compare the three groups according to nutritional status, parametric and non-parametric tests were applied. Significance level was set at p<0.05.RESULTS: There was no significant difference in resting heart rate, health-related physical fitness, relative body fat, absolute and relative lean mass, and health-related quality of life between overweight, obese, and severely obese adolescents (p>0.05). Body weight, body mass index, waist and hip circumference, and systolic blood pressure increased as degree of excess weightincreased (p<0.05). Dyastolic blood pressure of the severe obesity group was higher than the other groups (p<0.05). There was an association between the degree of excess weight and the prevalence of altered blood pressure (overweight: 12.1%; obesity: 28.1%; severe obesity: 45.5%; p<0.001). The results were similar when genders were analyzed separately.CONCLUSION: Results suggest that overweight adolescents presented similar results compared to obese and severely obese adolescents in most of the parameters analyzed.